Environmental Awareness, Knowledge, Product Quality and Green Product Purchase Decisions - Tarmizi, Achmad; Al Faruq Abdullah, Muhamad; Desty Febrian, Wenny; Hikmah Perkasa, Didin (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine the positive influence of environmental awareness, knowledge and product quality on decisions to purchase green products: Case Study of Consumers in the West Jakarta Region. Data collection in this research was carried out using a survey method by distributing 150 questionnaires using the sampling technique used. In this research, accidental sampling technique was used. The accidental sampling technique is the withdrawal of a sample size if the exact population size is not known. This research uses multiple regression analysis with the SPSS version 26 program as a tool for processing and analyzing research results. The results of the hypothesis test show that the Environmental Awareness variable has a significant effect on Green Product Purchasing Decisions. The knowledge variable has a significant effect on Green Product Purchasing Decisions. The product quality variable has a significant effect on green product purchasing decisions. And the variables environmental awareness, knowledge and product quality together (simultaneously) have a significant effect on green product purchasing decisions.